Pengembangan Kurikulum Terpadu Pendidikan Agama Islam Sistem Full Day School (Studi di Madrasah Ibtidaiyah Al-Mu’minin Kabupaten Ciamis dan Sekolah dasar Islam Terpadu Insantama Kota Banjar) - Ismail, Norman; Sumadi, Sumadi (Graduate Program, Universitas Islam Darussalam (UID) | Islamic University of Darussalam, 2018)
This article demonstrates several research results: First, education planning begins by accommodating parents' wishes, developing vision, mission, and objectives, developing a quality assurance system, developing strategic plans, and formulating program and program assessment instruments. Second, the curriculum is based on national curriculum and local content curriculum. Third, the implementation of learning is based on exemplary method, lecture method, method of habituation, assignment method, environment creation method, tourism work method, storytelling method, storytelling, discussion method, and simulation method. Fourth, the evaluation of learning is focused on the results of the control card or the absence of activities, the activity of the students, and the behavior and character of the students